Observation of Bottom‐Trapped Topographic Rossby Waves on the Shelf Break of the Chukchi Sea. Issue 7 (12th July 2020) - Ku, Ahyoung; Seung, Young Ho; Jeon, Chanhyung; Choi, Youngseok; Yoshizawa, Eri; Shimada, Koji; Cho, Kyoung‐Ho; Park, Jae‐Hun
Abstract: This study investigates topographic Rossby waves (TRWs) with a period of approximately 35 hr using a mooring observation at 194‐m depth on the shelf break of the Chukchi Sea in the Arctic Ocean. We measured velocity, temperature, and salinity for about 1 year from August 2014 to August 2015. The observations reveal that the bottom‐intensified upslope current fluctuations were significantly coherent with near‐bottom temperature fluctuations, with a phase lag of approximately 90°. Near the seafloor, the temperature increased with depth. Therefore, the temperature increases (decreases) with the upslope (downslope) currents. Theoretical estimates of the wavelength, angle of wavenumber vector, and bottom‐trapping depth confirmed that the observed near 35‐hr TRWs are indeed plausible in the study area. Energetic TRWs were observed in September and October, during the sea ice free season, whereas weak TRWs were observed in months with sea ice cover. The TRW events coincided with local wind‐stress events, suggesting that the TRWs were triggered by atmospheric forcing. These findings imply that a longer ice‐free season may allow for a more frequent occurrence of energetic TRWs, which may enhance the water exchange between the shallow continental shelf and the deep ocean. Plain Language Summary: A year‐long time series of velocity and temperature showed fluctuations occurring every 35 hr in a shelf region of the western Arctic Ocean, located downstream of where Pacific Water flows into the Arctic through Bering Strait. Fluctuations were the strongest near the seabed on the shelf. Temperature fluctuations were found to be caused by vertical displacements of about 40 m of water parcels on the sloping topography. These features were consistent with topographic Rossby waves (TRWs), which are waves affected by bottom slope and stratification effects over sloping seabed. We used theoretical models to estimate wavelength and propagation angle using the local bottom slope and stratification. We also found that TRW events coincided with strong wind‐stress events and were strong during the sea ice‐free season and weak during the sea ice‐covered season. These findings imply that a longer ice‐free season may allow for a more frequent occurrence of wind‐generated energetic TRWs, and this may lead to environmental changes in the shelf regions of the western Arctic Ocean. Key Points: Topographic Rossby waves with an ~35‐hr period were observed on the shelf break of the Chukchi Sea Key wave features included bottom‐intensified fluctuations and significant coherence between near bottom temperature and upslope velocity Topographic Rossby wave events were found to coincide with strong wind‐stress events, suggesting that they are triggered by wind forcing